TO EVALUATE EFFECTIVENESS OF COPING STRATEGIES OF MENOPAUSE AMONG MENOPAUSAL WOMEN - Prof. DR.J.RUKUMANI (International Journal of Pharma and Bio Sciences, 2015)
A evaluative study on effectiveness of coping strategies of menopause among menopausal women at Pondicherry. 500 sample were selected by stratified random sampling technique. The findings shows high significant in the coping strategies among menopausal women after implementing coping strategies.